Contributors to the substantial variation in on‐treatment testosterone levels in men receiving transdermal testosterone gels in randomized trials. (5th October 2017) - Bhasin, S.; Travison, T. G.; O'Brien, L.; MacKrell, J.; Krishnan, V.; Ouyang, H.; Pencina, K.; Basaria, S.
Summary: There is substantial inter‐individual variability in serum testosterone levels in hypogonadal men treated with testosterone gels. We aimed to elucidate participant‐level factors that contribute to inter‐individual variability in testosterone levels during testosterone therapy. An exploratory aim was to determine whether polymorphisms in genes encoding testosterone‐metabolizing enzymes could explain the variation in on‐treatment testosterone concentrations in men who were randomized to testosterone arm in TOM Trial. We used data from three randomized trials that used 1% transdermal testosterone gels and had testosterone levels measured 2–4 weeks after randomization for dose adjustment: Testosterone in Older Men with Mobility Limitation (TOM), Effects of Testosterone on Pain Perception (TAP), and Effects of Testosterone on Atherosclerosis Progression (TEAAM). Forty‐seven percent, 38%, and 9% of participants in TAP, TEAAM, and TOM trials, respectively, failed to raise testosterone levels >400 ng/dL; 6, 8, and 30% of participants had on‐treatment testosterone levels >1000 ng/dL. Even after dose adjustment, there was substantial variation in on‐treatment levels at subsequent study visits. Baseline characteristics (age, height, weight, baseline testosterone, SHBG, hematocrit, and creatinine) accounted for only a small fraction of the variance (<8%). Polymorphisms in SHBG and AKR1C3 genes were suggestively associated with on‐treatment testosterone levels. To conclude, baseline participant characteristics account for only a small fraction of the variance in on‐treatment testosterone levels investigated. Multiple dose titrations are needed to maintain on‐treatment testosterone levels in the target range. The role of SHBG and AKR3C1 polymorphisms as contributors to variations in on‐treatment testosterone levels should be investigated.